EPONIMIC NAMES OF SPHINCTERS AND STRUCTURES OF THE GASTROINTESTINAL TRACT - Світлицький, А.О. (World of Medicine and Biology, 2015)
This paper provides information about the sphincters of the gastrointestinal tract, their location, structure as well as historical information about scientists namesake those or other structures. Total provides information about 29 sphincters description produced in series, in the course of the gastrointestinal tract.
Keywords: eponyms; gastrointestinal tract; sphincters